The Revolution of Arabic Language Learning: Integration of Digital Technology in 21st Century Education - Hady, Rosli; Nasri, Ulyan; Hajras, Multazam; Hasyim, Muhammad; Rahmatullah, Ali Jumaah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The integration of digital technology into Arabic language education has become increasingly relevant in the context of 21st-century learning, especially in addressing challenges such as low student interest and the perception that Arabic is a difficult subject. This study aims to explore the integration of digital technology in Arabic language learning within Islamic boarding schools. A mixed-methods approach was employed, combining quantitative data from surveys with 100 female students and 4 Arabic teachers from two institutions at Pondok Pesantren Syaikh Zainuddin NW Anjani, and qualitative data from semi-structured interviews and classroom observations. Quantitative data were analyzed using descriptive statistics, while qualitative data were thematically analyzed. The results show that both students and teachers generally perceive technology positively in Arabic learning. It enhances motivation, expands access to resources, encourages collaborative learning, and allows for personalized instruction. Nevertheless, challenges include limited access to devices, inadequate quality of digital content, and insufficient digital competencies among teachers. In conclusion, the integration of digital technology holds great promise for improving Arabic language instruction, provided there is sufficient institutional investment in infrastructure and teacher training.